Mafic rocks of the Ordovician Famatinian magmatic arc (NW Argentina): New insights into the mantle contribution - Alasino, Pablo H. (2016)
We studied the petrogenesis of mafic igneous rocks in the Famatinian arc in the western Sierra Famatina (NW Argentina), an Early Ordovician middle-crustal section in the proto-Andean margin of Gondwana. Mafic rock types consist of amphibolite, metagabbro, and gabbro, as well as pod- and dike-like bodies of gabbro to diorite composition. Field relations together with geochemical and isotopic data for the mafic rocks of the western Sierra de Famatina (at 29°S) define two contrasting suites, which can be correlated with similar assemblages noted in other parts of the orogen. Amphibolite, metagabbro, and gabbro bodies are mostly the oldest intrusive rocks (older than 480 Ma), with the host tonalite and post-tonalite mafic dikes being slightly younger. The older mafic suite is tholeiitic to calc-alkaline and isotopically evolved, except for most of the amphibolite samples. The younger suite is calc-alkaline, typically displaying subduction-related geochemical signatures, and it is isotopically more juvenile. Whole-rock chemical composition and isotopic analyses are compatible with a progressive mixing of different isotopic reservoirs. Pyroxenite (±garnet) was likely the dominant source of the older gabbroic magmas, whereas peridotite dominated in the source of the younger suite, implying that the mafic magma experienced a progressive shift toward more juvenile compositions though time (over 20 m.y.). Pyroxenitederived melts could have been generated by lithospheric foundering followed by upwelling of primitive melts by adiabatic decompression of mantle wedge peridotite.